Faktor-Faktor yang Mempengaruhi Konsumen dalam Memilih Produk Halal - Permana Putra, Anan; Andriani, Novie (Institut Agama Islam YPBWI Surabaya, 2023)
This study aims to analyze the factors that influence consumers in choosing halal products. This research was conducted by collecting information based on the result of interviews regarding the factors that influence consumer in choosing halal products with reference to several related theories. The result of this study can be seen that the factors that influence consumers in choosing halal products are derived from religious principles, environmental, and health factors. On the other hand, the government is role in implementing halal certification and labeling regulations also has an effect on making it easier for consumers to choose halal product.